Husband material eaudiobook - Hall, Alexis (London Calling, 2022)
In Boyfriend Material, Luc and Oliver met, pretended to fall in love, fell in love for real, dealt with heartbreak and disappointment and family and friends...and somehow figured out a way to make it work. Now it seems like everyone around them is getting married, and Luc's feeling the social pressure to propose. But it'll take more than four weddings, a funeral, and a bowl full of special curry to get these two from I don't know what I'm doing to I do. Good thing Oliver is such perfect Husband Material.